2016
DOI: 10.1002/pbc.26118
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of young children with high‐grade glioma treated with irradiation‐avoiding intensive chemotherapy regimens: Final report of the Head Start II and III trials

Abstract: Purpose To report the final analysis of survival outcomes for children with newly diagnosed high-grade glioma (HGG) treated on the “Head Start” (HS) II and III protocols with chemotherapy and intent to avoid irradiation in children <6 years old. Patients and Methods Between 1997 and 2009, 32 eligible children were enrolled in HS II and III with anaplastic astrocytoma (AA, n = 19), glioblastoma multiforme (GBM, n = 11), or other HGG (n = 2). Central pathology review was completed on 78% of patients. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“… 8 , 9 , 11 Young children treated with cranial irradiation experience devastating neurocognitive sequelae and tumor recurrence; however, there is growing evidence that younger patients (< 36 months old) demonstrate longer event-free and overall survival when treated with single-cycle induction chemotherapy consisting of vincristine, carboplatin, and temozolomide. 12 However, progression-free survival rates remain poor for these patients, highlighting the need for new therapeutic options, including small molecules and/or immunotherapy alone or in combination with chemotherapy regimens. 13 Although the etiology and genomic drivers of glioblastoma are diverse, 14 - 16 a common finding in pediatric HGG, especially infantile HGGs, is the presence of fusions involving NTRK , ALK , and ROS1 , among others.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 11 Young children treated with cranial irradiation experience devastating neurocognitive sequelae and tumor recurrence; however, there is growing evidence that younger patients (< 36 months old) demonstrate longer event-free and overall survival when treated with single-cycle induction chemotherapy consisting of vincristine, carboplatin, and temozolomide. 12 However, progression-free survival rates remain poor for these patients, highlighting the need for new therapeutic options, including small molecules and/or immunotherapy alone or in combination with chemotherapy regimens. 13 Although the etiology and genomic drivers of glioblastoma are diverse, 14 - 16 a common finding in pediatric HGG, especially infantile HGGs, is the presence of fusions involving NTRK , ALK , and ROS1 , among others.…”
Section: Discussionmentioning
confidence: 99%
“…3 Many respond to chemotherapy, however RT is with-held due to the impact of radiation therapy in infants. 4 Treatment with RT may be used at recurrence, but with devastating sequelae. Progression following RT leads to a dismal outcome.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Several studies using HDCT/auto-SCT to minimize RT, including Head Start I-III and CCG 99703, have reported encouraging outcomes in very young patients with malignant brain tumors. 8 9 10 11 12 13 14 Previously, we also reported encouraging preliminary results of a single-arm trial using tandem HDCT/auto-SCT in very young children with malignant brain tumors. However, the number of enrolled patients was small, and the short follow-up duration prevented analysis of long-term late effects.…”
Section: Discussionmentioning
confidence: 74%
“… 5 6 7 Following success in high-risk neuroblastoma, studies have investigated the effectiveness of HDCT/auto-SCT in improving the prognosis of high-risk brain tumors and/or to avoid or minimize RT. 8 9 10 11 12 Recently, it has been demonstrated that further dose intensification by tandem HDCT/auto-SCT may further improve outcomes in patients with high-risk brain tumors. 13 14 …”
Section: Introductionmentioning
confidence: 99%